Comparison of shear bond strength of aesthetic restorative materials - B P Suryakumari Nujella; Manisha T Choudary; Satyanarayana P Reddy; M Kiran Kumar; T Gopal (Wolters Kluwer Medknow Publications, 2012)
Aim : The present study was conducted to determine and compare the shear bond strengths of Conventional glass ionomer; Resin-modified glass ionomer; Polyacid-modified composite and Composite Resin, and to assess and determine the mode of failure (adhesive, cohesive, mixed). Materials and Methods : Occlusal dentin of 40 extracted human teeth were randomly divided into four groups of ten teeth, each based on the restorative materials tested as follows: Group I: Conventional Glass Ionomer Cement (Control); Group II: Resin-modified Glass Ionomer Cement; Group III: Polyacid-modified Composite Resin; Group IV: Hybrid Composite Resin. The bonded materials were subjected to shear bond strength (SBS) testing in a Instron Universal Testing Machine (UTM) at a crosshead speed of 0.5 mm/min. The bond failure location was examined by the use of a stereomicroscope at 10× magnification. The mean SBS of Groups I-IV obtained was 3.81, 9.71, 11.96 and 18.16 MPa, respectively. Comparison of mean shear bond strengths of all groups was done by one way ANOVA test and comparison of means in between groups by the Student's t test. Conclusion : It is concluded that the compomer restorative materials show higher shear bond strength than conventional glass-ionomer and resin-modified glass-ionomer, but less than composite resin.